Biogenic Sulfur in the Siple Dome Ice Core - Dioumaeva, Irina; Finley, Brandon; Saltzman, Eric (IEDA: US Antarctic Program Data Center, 2004)
This data set is a continuous, high-resolution record of biogenic sulfur (methanesulfonate, known as MSA and CH3SO3-) in the 1000 m deep Siple Dome A (SDMA) core, covering 100,000 to 20 years BP. The analysis was done on between August 2002 and November 2003 at the University of California, Irvine. Investigators used a mass spectrometer to measure methanesulfonate. Measurements are given as MSA concentration at various depths. Estimated age of the ice at each depth is also given. This project was a part of the West Antarctic Ice Sheet Cores (WAISCORES) project for deep ice coring in West Antarctica. WAISCORES is supported by the Office of Polar Programs, National Science Foundation (NSF).